Addressing the mental health impact of COVID-19 through population health. (April 2021) - Boden, Matt; Zimmerman, Lindsey; Azevedo, Kathryn J.; Ruzek, Josef I.; Gala, Sasha; Abdel Magid, Hoda S.; Cohen, Nichole; Walser, Robyn; Mahtani, Naina D.; Hoggatt, Katherine J.; McLean, Carmen P.
Abstract: The COVID-19 pandemic has and will continue to result in negative mental health outcomes such as depression, anxiety and traumatic stress in people and populations throughout the world. A population mental health perspective informed by clinical psychology, psychiatry and dissemination and implementation science is ideally suited to address the broad, multi-faceted and long-lasting mental health impact of the pandemic. Informed by a systematic review of the burgeoning empirical research on the COVID-19 pandemic and research on prior coronavirus pandemics, we link pandemic risk factors, negative mental health outcomes and appropriate intervention strategies. We describe how social risk factors and pandemic stressors will contribute to negative mental health outcomes, especially among vulnerable populations. We evaluate the scalability of primary, secondary and tertiary interventions according to mental health target, population, modality, intensity and provider type to provide a unified strategy for meeting population mental health needs. Traditional models, in which evidence-based therapies delivered are delivered in-person, by a trained expert, at a specialty care location have proved difficult to scale. The use of non-traditional models, tailoring preventive interventions to populations based on their needs, and ongoing coordinated evaluation of intervention implementation and effectiveness will be critical to refining our efforts to increase reach. Highlights: The COVID-19 pandemic will broadly and substantially impact the mental health of populations worldwide. Social determinants will heighten the impact of pandemic stressors among particular populations. With a population health perspective, we link mental health risks, negative outcomes and interventions. We provide a framework matching primary, secondary and tertiary targets to appropriate interventions. Scalability of interventions is impacted by target, population, modality, intensity and provider type.